The Design Challenges for Dog Ownership and Dog Walking in Dense Urban Areas: The Case of Japan - Koohsari, Mohammad Javad; Yasunaga, Akitomo; McCormack, Gavin R.; Nakaya, Tomoki; Nagai, Yukari; Oka, Koichiro (Frontiers in Public Health, 2022)
There has been growing interest in the role of pet ownership, particularly dog ownership, in managing noncommunicable diseases. The built environment can act as a facilitator or barrier to owning a dog or dog walking. Nevertheless, limited studies conducted in different geographical contexts have examined how the built environment can influence dog ownership and dog walking. In this interdisciplinary article, using Japan as a case study, we identify key design challenges to owning and walking dogs in dense urban areas as a means of promoting health and wellbeing.